2021
DOI: 10.1111/2041-210x.13567
|View full text |Cite
|
Sign up to set email alerts
|

Telemetry‐validated nitrogen stable isotope clocks identify ocean‐to‐estuarine habitat shifts in mobile organisms

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
29
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 40 publications
(106 reference statements)
0
29
0
Order By: Relevance
“…This differs from more typical isotopic applications to ecology, which generally use δ 15 N to estimate trophic dynamics and δ 13 C to trace energy source and foraging location(s), due to lower trophic fractionation of δ 13 C than of δ 15 N (Post, 2002). However, more recent studies have demonstrated that in some systems and for certain predators, baseline δ 15 N values across ecoregions can result in predators acquiring regional δ 15 N signatures that outweigh trophic effects (Graham et al, 2010;Hobson et al, 2010;Madigan et al, 2017;Shipley et al, 2021). Isoscapes will be basin-and ecosystemdependent.…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations
“…This differs from more typical isotopic applications to ecology, which generally use δ 15 N to estimate trophic dynamics and δ 13 C to trace energy source and foraging location(s), due to lower trophic fractionation of δ 13 C than of δ 15 N (Post, 2002). However, more recent studies have demonstrated that in some systems and for certain predators, baseline δ 15 N values across ecoregions can result in predators acquiring regional δ 15 N signatures that outweigh trophic effects (Graham et al, 2010;Hobson et al, 2010;Madigan et al, 2017;Shipley et al, 2021). Isoscapes will be basin-and ecosystemdependent.…”
Section: Discussionmentioning
confidence: 93%
“…While SI-inferred movements are limited by isotopic turnover rates of analyzed tissue, prior movements can be characterized due to mobile predators integrating prey isotopic signatures during movements through isotopically distinct regions (Graham et al, 2010;MacKenzie et al, 2012;Carlisle et al, 2015;Madigan, 2015;Trueman and Glew, 2019). As such, isotope-and tag-inferred migration patterns are effective complementary techniques (Carlisle et al, 2012(Carlisle et al, , 2015Madigan et al, 2015Madigan et al, , 2018Shipley et al, 2021). Here, comparing isotopic estimates to past conventional tagging suggests that blue sharks make both eastward and westward trans-Pacific migrations, though the number of sharks that make these migrations appears to be low (<5%).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Most animals move across certain areas when foraging and/or over the course of their growth. To date, isotopic studies that considered λ explicitly in their inferences have investigated individuals migrating between isotopically distinct habitats [ 33 , 34 ] and individuals exploiting seasonally available resources [ 35 ]. The combination of ontogenetic shifts, suboptimal physiological states of consumers, changes in availability and/or quality of prey resources [ 21 ], and habitat use impact δ c , highlighting λ as a key parameter for the integration time of the incorporated δ s , to track animal movements and niche shifting [ 30 , 36 , 37 ].…”
Section: Introductionmentioning
confidence: 99%